Probing ultrafast processes by fifth order Stimulated Raman Scattering. (February 2016) - Fumero, G; Batignani, G; Dorfman, K E; Mukamel, S; Scopigno, T
Abstract: We present the full diagrammatic description of non-resonant impulsive femtosecond stimulated Raman spectroscopy in a multimode model system. In this technique the pump-probe scheme is exploited to study the vibrational structure of the sample via stimulated Raman scattering. We apply closed-time-path-loop diagrams to calculate the complete response of the system at the relevant perturbation order. We show that, in presence of low-frequency modes, coherences created by the impulsive pump modify the resulting Raman signal, which oscillates from gain to loss features, depending on the time delay between the pump and probe pulses. This leads to a redistribution of photons among the fields involved in the process and, consequently, the energy flows between fields and matter. Moreover, through this formalism, we address the case of extremely short delays in which the pump and probe fields overlap in time. We find that, even in absence of photo-induced dynamics due to absorption of the pump pulse, the overlap condition can generate time dependent features, arising from additional diagrams, which offer no contribution for well separated pulses.